Relationship between Antiviral Activity and Host Toxicity: Comparison of the Incorporation Efficiencies of 2′,3′-Dideoxy-5-Fluoro-3′-Thiacytidine-Triphosphate Analogs by Human Immunodeficiency Virus Type 1 Reverse Transcriptase and Human Mitochondrial DNA Polymerase - Feng, Joy Y. (American Society for Microbiology, 2004)
Emtricitabine [(−)FTC; (−)-β-l-2′-3′-dideoxy-5-fluoro-3′-thiacytidine] is an oxathiolane nucleoside analog recently approved by the Food and Drug Administration for the treatment of human immunodeficiency virus (HIV). Structurally, (−)FTC closely resembles lamivudine [(−)3TC] except that the former is 5-fluorinated on the cytosine ring. In HIV-1 reverse transcriptase (RT) enzymatic assays, the triphosphate of (−)FTC [(−)FTC-TP] was incorporated into both DNA-DNA and DNA-RNA primer-templates nearly 3- and 10-fold more efficiently than (−)3TC-TP. Animal studies and clinical trial studies have demonstrated a favorable safety profile for (−)FTC. However, a detailed study of the incorporation of (−)FTC-TP by human mitochondrial DNA polymerase γ, a host enzyme associated with nucleoside toxicity, is required for complete understanding of the molecular mechanisms of inhibition and toxicity. We studied the incorporation of (−)FTC-TP and its enantiomer (+)FTC-TP into a DNA-DNA primer-template by recombinant human mitochondrial DNA polymerase in a pre-steady-state kinetic analysis. (−)FTC-TP was incorporated 2.9 × 10(5)-, 1.1 × 10(5)-, 1.6 × 10(3)-, 7.9 × 10(3)-, and 100-fold less efficiently than dCTP, ddCTP, (+)3TC-TP, (+)FTC-TP, and (−)3TC-TP, respectively. The rate of removal of (−)FTC-MP from the corresponding chain-terminated 24-mer DNA by polymerase γ's 3′→5′ exonuclease activity was equal to the removal of (+)FTC-MP, 2-fold slower than the removal of (−)3TC-MP and (+)3TC-MP, and 4.6-fold slower than the excision of dCMP. These results demonstrate that there are clear differences between HIV-1 RT and polymerase γ in terms of preferences for substrate structure.